O brincar de crianças de 0 a 5 anos de idade durante o isolamento social provocado pela COVID-19 - Fernandes, Beatriz Palma (Universidade Federal de São Carlos, 2023)
As a result of the pandemic caused by the SARS-COV-2 virus, in 2020, Brazilian schools had their face-to-face activities suspended and children were confined to their home space, adapting to a new reality. As the literature points out, play activities play an important role in children's development and learning and, for this reason, this study aims to understand how children aged zero to five years old played during this period of social isolation. This is a part of an inter-institutional research carried out between the Federal University of São Carlos (UFSCar) and the Paulista State University "Júlio de Mesquita Filho" (UNESP), under CEP number 4.683.194, which investigated how children up to five years of age played during the quarantine period in Brazil. Qualitative-quantitative character (CRESWELL, 2007), this research had, at first, a bibliographic survey about the pandemic and the children's play in this context of social isolation, in which they needed to adapt to a new teaching model, that of remote classes, held in their home environment. Subsequently, a bibliographic research was carried out, anchored in authors such as Vigotsky, Kishimoto, Brougère, Chateau, Huizinga, Sommerhalder, Alves and Arce in order to structure concepts around playfulness and highlight its importance for child development and learning. In a last moment, the answers to a Survey questionnaire were analyzed, applied using the Google Forms platform, in which a total of 238 guardians of children up to five years of age, who did not attend school due to measures to cope with the coronavirus disease, answered questions related to the context of the games and games that took place in this atypical period. Based on the Content Analysis method proposed by Lawrence Bardin (1979), we elaborated three categories a posteriori. The first, called "Playing spaces", presents the different spaces in which play was experienced during this pandemic period, bringing reflections on playing inside and outside domestic environments. In the second category, "With whom to play", we present the subjects with whom the children played in the analyzed period, demonstrating the importance of the other for their development and learning. In the third and last category, called "What to play", we address the main games experienced by children, which reflect their play culture. Among the conclusions, we show that, most of the time, due to the restrictions imposed, children did not have friends with whom to share moments of playfulness and had to learn to play alone, in some of these moments only with adults, usually parents and relatives, with whom they experienced social isolation.
The playing of children from 0 to 5 years old during the social isolation caused by COVID-19
El juego de los niños de 0 a 5 años durante el aislamiento social por el COVID-19
Keywords: Criança; Brincar; Família; Child; Play; Family; COVID-19; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM